Мактаб ўқувчилар жисмоний тайёргарлигининг йиллик динамикаси - Бахриддинов, Ҳ.З. (SCIENCE and SOCIETY, 2020)
The article examines the annual dynamics of physical characteristics of students aged 14-15 in high school, such as speed, strength, speed, strength and endurance.